ASSESSMENT OF FIREFIGHTING EFFICIENCY OF VEGETATION FIRES IN CURITIBA-PARANÁ - Ferreira, Heitor Renan; Batista, Antonio Carlos; Tetto, Alexandre França (Floresta, 2021)
Vegetation fires, when not controlled, cause economic disruption, temporary loss of vegetation, and damage to soil, fauna and health. To improve the process of fire prevention and firefighting, it is necessary to evaluate the performance of the involved agents. The objective of this study was to evaluate the firefighting efficiency of vegetation fires in the municipality of Curitiba, Paraná, from 2011 to 2015, using records from the Fire Department of the Military Police of Paraná. Once the consistency of the fire records was verified, they were classified and information was gathered regarding the extent of burnt area, time of first attack, combat time, main fire-extinguishing methods used, and amount of water used. The results indicate that 88% of the records registered a burnt area inferior or equal to four hectares. In addition, the mean burnt area was of 2,399.21 m², the mean attack time was of 14.1 minutes, and the mean combat time was of 29.9 minutes, all lower than the ones presented by studies from different locations. As for the fire-extinguishing methods, it was verified that smothering equipment and water were used in 66.4 and 60.6% of the records, respectively. The mean amount of water used was of 1,186.56 liters per fire, indicating a minimum volume necessary for water storage containers for firefighting in the study area. Based on the results, we concluded that the firefighting of vegetation fires in Curitiba is efficient.